The economic value of knowing BRCA status: universal BRCA testing for breast cancer prevention. (16th March 2023) - Oh, Mok; McBride, Ali; Bhattacharjee, Sandipan; Slack, Marion; Jeter, Joanne; Abraham, Ivo
ABSTRACT: Background: This study aimed to estimate the incremental lifetime effects, costs, and net monetary benefit (NMB) of knowing BRCA information by universal genetic testing of all US women without breast cancer turning 40 in a given year, and the cumulative savings or losses of yearly cohort testing over 16 years. We compared two strategies: (1) 'with BRCA information' and (2) 'without BRCA information.' Methods: Incremental NMB (INMB) was calculated as the monetized benefit per person of knowing BRCA status. The net monetized value (cumulated INMB) of knowing BRCA information was estimated by multiplying the INMB with the eligible population or the year 2020 cohort of US women age 40 and extended for a total of 16 yearly cohorts. Results: Universal testing of the female population at the age of 40 in a given year provided aan INMB of 663/person (payer) and 1, 006/person (society).Escalated to the U.S. population of women age 40, knowing BRCA status resulted in lifetime cumulated INMB of 1.3 billion (payer) and 2.0 billion (society) for the 2020 cohort; and yielded accumulated monetized value of 18.3 billion (payer) and 27.6 billion (society) over 16 yearly cohorts of 40-year-old women. Conclusions: The universal testing for BRCA status of all US women at age 40 provides compelling short-term and long-term economic value.